2016
DOI: 10.1177/2165143416633426
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of a Science, Technology, Engineering, and Mathematics Mentoring Program

Abstract: Individuals with disabilities are underrepresented in science, technology, engineering, and math (STEM) fields. The purpose of this study was to experimentally evaluate the impact of a STEM mentor intervention and differences between students matched with mentors with or without disabilities on career planning outcomes. An independent groups × repeated measures design was used. Significant differences were found between mentored and nonmentored students for measures of STEM-related knowledge, engagement, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Although the present study examined only match outcomes, the quantitative data suggested that disability similarity may be less important than commonly thought and did not confirm the hypotheses regarding the benefits of matching on the basis of disability similarity. Consistent with these findings on the lack of a positive effect of disability similarity on outcomes, a recent study examined youth outcomes for mentees with a disability and reported no differences between youth matched with a mentor having similar disability challenges and youth matched with a mentor who had no disability (Sowers et al., ). Taken together, these studies suggest that other factors or other similarity characteristics besides shared disability status may be more important for producing positive match and youth outcomes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although the present study examined only match outcomes, the quantitative data suggested that disability similarity may be less important than commonly thought and did not confirm the hypotheses regarding the benefits of matching on the basis of disability similarity. Consistent with these findings on the lack of a positive effect of disability similarity on outcomes, a recent study examined youth outcomes for mentees with a disability and reported no differences between youth matched with a mentor having similar disability challenges and youth matched with a mentor who had no disability (Sowers et al., ). Taken together, these studies suggest that other factors or other similarity characteristics besides shared disability status may be more important for producing positive match and youth outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…One study examined the effect of matching on disability by randomly assigning students with one of several types of disabilities to have a mentor either with or without a disability or to a no-treatment control group (Sowers et al, 2016).…”
Section: Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…• One methodologically sound group design study with random assignment (Sowers et al, 2017) Multimodal Anxiety and Social Skills Intervention (MASSI)…”
Section: Ebpsmentioning
confidence: 99%
“…Nevertheless, Britner et al [39] concluded that matching based on having similar disability might only benefit mentees who have not been exposed to positive role models with similar disabilities previously. Specifically, one study did randomly assign students with a wide variety of disabilities to either a mentor with or without similar disability-challenges or a control group, but no differences in youth outcomes were found [46]. While the results of these previous studies do not indicate that having a mentor with a similar disability confers benefits to their mentees, this had not been tested for youth with a visual impairment using mentors with and without a visual impairment.…”
Section: Mentoring For Youth With Disabilitiesmentioning
confidence: 99%